Left atrial late gadolinium enhancement in patients with ischaemic stroke. (24th January 2023) - Larsen, Bjørn Strøier; Bertelsen, Litten; Christensen, Hanne; Hadad, Rakin; Aplin, Mark; Høst, Nis; Christensen, Louisa Marguerite; Havsteen, Inger; Prescott, Eva; Dominguez, Helena; Jensen, Gorm Boje; Vejlstrup, Niels; et al.
Abstract: Aims: To evaluate the extent of left atrial (LA) fibrosis in patients with a recent stroke without atrial fibrillation and controls without established cardiovascular disease. Methods and results: This prospectively designed study used cardiac magnetic resonance to detect LA late gadolinium enhancement as a proxy for LA fibrosis. Between 2019 and 2021, we consecutively included 100 patients free of atrial fibrillation with recent ischaemic stroke (<30 days) and 50 age- and sex-matched controls. LA fibrosis assessment was achieved in 78 patients and 45 controls. Blinded to the cardiac magnetic resonance results, strokes were adjudicated according to modified Trial of Org 10172 in Acute Stroke Treatment classification as undetermined aetiology ( n = 42) or as attributable to large- or small-vessel disease ( n = 36). Patients with stroke had a larger extent of LA fibrosis [6.9%, interquartile range (IQR) 3.6–15.4%] than matched controls (4.2%, IQR 2.3–7.5%; P = 0.007). No differences in LA fibrosis were observed between patients with stroke of undetermined aetiology and those with large- or small-vessel disease (6.6%, IQR 3.8–16.0% vs. 6.9%, IQR 3.4–14.6%; P = 0.73). Conclusion: LA fibrosis was more extensive in patients with stroke than in age- and sex-matched controls. A similar extent of LA fibrosis was observed in patients with stroke of undetermined aetiology and stroke classified as attributable to large- or small-vessel disease. Our findings suggest that LA structural abnormality is more frequent in patients with stroke than in controls independent of aetiological classification. Graphical Abstract: Graphical Abstract